Comparable analysis of the influence of rotary file system with reciprocating file system on postobturation pain after single-sitting endodontics: A randomized clinical study - Anshu Vij; Shweta Verma; Sadaf Ahmed; Richa Sharma; Pallavi Kumari; Danish Qureshi (Wolters Kluwer Medknow Publications, 2023)
Aim: The objective of this study was to determine the influence of various factors (sex, class, and arch of tooth) on postoperative pain (PP) after use of Rotary ProTaper Gold (PTG) and Reciprocating WaveOne Gold (WOG) file system following single-visit endodontic treatment. Materials and Methods: One hundred and twenty patients requiring endodontic therapy were assessed for the study. Permanent posterior teeth with acute irreversible pulpitis and vital pulp were selected. Patients were blindly grouped and analyzed based on the files employed for single-visit endodontic treatment: "Group 1" (n = 60) was treated using PTG and "Group 2" (n = 60) in which WOG was used during biomechanical preparation. Patients selected were instructed to record the before and after treatment pain incidence using a Modified Verbal Descriptive Scale at 12, 24, and 48 h. Chi-square and Fisher's exact tests were used for the data analysis (P ≤ 0.05). Results: Postobturation pain (PP) after single-visit root canal treatment using PTG and WOG showed a higher proclivity for females with a greater predilection for maxillary posteriors mainly premolars. Comparing PTG with WOG, the latter showed significantly less PP after 12 h (P = 0.559), 24 h (P = 0.559), and 48 h (P = 0.556), although the difference between the two was insignificant (P > 0.05). Conclusion: Postobturation pain incidence was higher when canals were instrumented with PTG than WOG file system following single-visit endodontics.